Acceptance of a COVID-19 Vaccine Before it is Available in China During the Pandemic - Xu, Jian; Liu, Cong (International Journal of Public Health, 2021)
Objectives: This study aims to explore the Chinese acceptance of a COVID-19 vaccine before it is available as well as its determinants. Methods: A cross-national online survey was conducted covering all 31 provinces of mainland China. The survey consists of the demographic variables, acceptance of a self-paid COVID-19 vaccine as the dependent variable, and the 3Cs factors (i.e., confidence, convenience, and complacency) as the independent variables. Results: Among the 1532 participants, 57.9% accepted to get a self-paid COVID-19 vaccine. COVID-19 vaccine acceptors were more likely to be concerned about the effectiveness of the vaccines, believe that they were at risk of COVID-19 infection, have a high perceived susceptibility of COVID-19, and trust in the health care system. Conclusion: Findings indicate that the critical task in the early stage of the COVID-19 vaccine development in China is to increase the tolerance to some intuitive concerns about the vaccines, put more emphasis on the communication of the saliency of the disease threats, and effectively translate people’s trust in the government into vaccine acceptance.